Career aspiration, job demands and social interest as predictors of job satisfaction of secondary school teachers (2013)
This study examines how career aspiration, job demands and social interest predict job satisfaction of secondary school Teachers. The study adopted a survey research design. Three hundred Secondary School teachers from Odeda Local Government Area, Ogun State responded to a set of questionnaires consisting of measures of Career Aspiration (a =.73), Job Demands (a =.84), Social Interest (a = .90) and Job Satisfaction (a =.98). Their age ranged between 24 and 55 years with mean age of 35.35years. Pearson’s Product Moment Correlation and Multiple regression analyses were used to analyses the data. The result shows that career aspiration and social interest were the potent predictors associated to teachers ’ job satisfaction. The study also reveals a significant relationship among career aspiration, job demands and social interest on the job satisfaction of teachers. The study has implications for the government and organisations responsible to the career developmental needs of teachers by providing career opportunities that match teachers ’ career aspirations. This will go a long way in making them get satisfy with their career, enhance efficiency and increase productivity. Intending teachers should consider the job demands of the profession in secondary schools; develop the required prerequisite before taking up teaching as a career.